Comparative analysis of ketone body metabolism in BALB/c mice infected with Trypanosoma evansi and Toxoplasma gondii. (March 2022) - Zhang, Zhaobo; Li, Yifan; Jiang, Ning; Sang, Xiaoyu; Han, Limei
Abstract: KBs (ketone bodies), i.e., acetoacetate, acetone, and ( R )-3-Hydroxybutanoate, constitute the intermediate products of the incomplete oxidative degradation of fatty acids. These KBs are used as a source of energy in the hosts' brain, skeletal muscles, and heart. Additionally, they regulate inflammation and oxidative stress of the host by acting as signaling mediators. Parasitic infection is known to result in abnormal physiological and biochemical metabolism, ketoacidosis, and other damage to the host. In this study, we investigated the effects of Trypanosoma evansi and Toxoplasma gondii on ketone body metabolism in mice, as well as the KB levels in the brain, liver, and peripheral blood. T. gondii was found to significantly increase the KB levels, resulting in ketonemia; T. evansi was found to stabilize KB levels in mice. Further investigations showed that T. evansi downregulated the expression of genes encoding enzymes involved in KBs synthesizing pathway and enhanced KBs synthesizing to eliminate ketonemia. Conversely, T. gondii significantly increased the expression of genes encoding enzymes involved in KBs synthesizing pathway and decreased KBs metabolism pathway ones and resulting in increased KBs levels in peripheral blood, culminating in ketonemia. These findings elucidate the differences in the KBs metabolism resulting from infection with T. evansi and T. gondii . Highlights: Design to build T. gondii and T. evansi infection animal mode l in BALB/c mice. T. gondii infection can significantly increase the KBs level and result in ketonemia, but T. evansi stabilized it in mice. Comparatives analyze the transcription level that encodes KBs synthesizing and metabolic pathway enzymes after T. evansi and T. gondii infection.